Cognitive functioning following brain irradiation as part of cancer treatment: Characterizing better cognitive performance. Issue 11 (30th August 2019) - Wong, Shan S.; Case, L. Douglas; Avis, Nancy E.; Cummings, Tiffany L.; Cramer, Christina K.; Rapp, Stephen R.
Abstract: Objective: Although brain radiation therapy (RT) impacts cognitive function, little is known about the subset of survivors with minimal cognitive deficits. This study compares the characteristics of patients receiving brain irradiation as part of cancer treatment with minimal cognitive deficits to those with poorer cognitive functioning. Methods: Adults at least 6 months postbrain RT (N = 198) completed cognitive measures of attention, memory, and executive functions. Cognitive functioning was categorized into better‐ and poorer‐performing groups, with better‐performing survivors scoring no worse than 1.5 standard deviations below the published normative mean on all cognitive measures. Logistic regression was used to identify variables associated with better‐performing group membership. Results: Approximately 25% of the sample met the criteria for the better‐performing group. In unadjusted analyses, RT type (whole brain irradiation and partial brain irradiation), sedating medications, and fatigue were independently associated with cognition. Sociodemographic and other clinical characteristics were not significant. In adjusted analyses, only fatigue remained significantly associated with group membership (OR = 1.05, 95% CI = 1.01‐1.09, P = .009). Conclusions: There is a subgroup of survivors with minimal long‐term cognitive deficits despite undergoing a full course of brain RT as part of cancer treatment. Lower fatigue had the strongest association with better cognitive performance. Interventions targeting cancer‐related fatigue may help buffer the neurotoxic effects of brain RT.